2008
DOI: 10.1007/s10646-008-0286-x
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase: a potential biochemical indicator for biomonitoring of fertilizer industry effluent toxicity in freshwater teleost, Channa striatus

Abstract: Monitoring of acetylcholinesterase (EC: 3.1.1.7, AChE) activity has been widely used in aquatic and terrestrial systems as an indicator of pollutant exposure. The reports regarding impact of fertilizer industry effluent on the level of AChE activity are very scanty. In this paper, an attempt has been made to investigate the in vitro impact of fertilizer industry effluent upon the levels of AChE activity and protein content in different tissues of non-target aquatic fish, Channa striatus (Bloch). The fish when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Arimoro (2009) reported a drastic reduction of benthic macroinverbrate species after the discharge effluent of a rubber industry. Yadav et al (2009) correlated the effect of effluents from the fertilizer industry with reduced levels of acetylcholinesterase from various organs of the fish species Channa striatus. Assessing the toxic effects of industrial effluents, Radic' et al (2010) observed growth inhibition and chlorophyll levels in duckweed (Lemna L. minor).…”
Section: Resultsmentioning
confidence: 99%
“…Arimoro (2009) reported a drastic reduction of benthic macroinverbrate species after the discharge effluent of a rubber industry. Yadav et al (2009) correlated the effect of effluents from the fertilizer industry with reduced levels of acetylcholinesterase from various organs of the fish species Channa striatus. Assessing the toxic effects of industrial effluents, Radic' et al (2010) observed growth inhibition and chlorophyll levels in duckweed (Lemna L. minor).…”
Section: Resultsmentioning
confidence: 99%
“…Many of these pollutants are persistent in the environment and are not readily biodegraded (Wepener et al, 2001;Yadav et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Acetylcholinesterase (AChE) has been used as a biomarker to determine neurotoxic contaminants in the aquatic environment (Yadav et al, 2009). AChE is the enzyme that catalyses the hydrolysis of the neurotransmitter acetylcholine, to form choline and acetic acid (Sakar et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations